ANALISIS KEBERHASILAN USAHA KELOMPOK NELAYAN PENERIMA BANTUAN JARING PAJEKO (PURSE SEINE) DI DESA DALUM KECAMATAN SALIBABU KABUPATEN KEPULUAN TALAUD - Dalope, Merlianti; Rarung, Lexy K.; Pontoh, Otniel (AKULTURASI: Jurnal Ilmiah Agrobisnis Perikanan, 2014)
Abstract This study analizes the success of the fishermen group’s venture as purse seine (pajeko) aid recipient in Dalum village salibabu sub district talaud island regency. This research is intended to study how this fishermen group, which is situated in Dalum village, and as purse seine aid recipient could success in their venture and looking at it from social and economic condition of the members of this fishermen group before before and after receiving the aid package, also about their organizational structure business management, capital, manpower, the yield of fish caught, marketing and product-sharing system. Based on the results of this studi, the social and economic condition of the above mentioned fishermen group’s members before and after receiving the aid package were already good. Since accordiny to engel index is 78,84% for food and fishermen rate of exchange (NTN) is around figure one (NTN=1), that is, 1,5 as still having remainder of income and the spending per month as much as 423,375 IDR. While after receiving the aid package, the member of the fishermen group as aid recipient having 59,59% of engel index for food and fisherman rate of exchange (NTN) around figure one (NTN=1), that is 1,8. This has been categorized as having quite good level of prosperity because one has been able to meet his/her daily livelihood and will have the potential of consuming secondary needs or even to save money with the rest of his income and monthly spending as much as 1.395.000 IDR Key words : fishermen group, the aid of purse seine (pajeko), Dalum village Abstrak Penelitian ini mengkaji tentang analisis keberhasilan usaha kelompok nelayan penerima bantuan jaring pajeko (purse seine) di Desa Dalum Kecamatan Salibabu Kabupaten Kepulauan Talaud. Penelitian ini bertujuan untuk mempelajari bagaimana keberhasilan kelompok nelayan penerima bantuan jaring pajeko (purse seine) di Desa Dalum yang dilihat dari kondisi sosial dan ekonomi anggota kelompok nelayan sebelum dan sesudah menerima paket bantuan, struktur organisasi, manajemen usaha, modal, tenaga kerja, hasil tangkapan, pemasaran dan sistim bagi hasil. Berdasarkan hasil penelitian kondisi sosial dan ekonomi anggota kelompok nelayan sebelum dan sesudah menerima paket bantuan sudah baik karena dari hasil analisis Indeks Engel sebelumnya adalah 78,84% untuk makanan dan Nilai Tukar Nelayan (NTN) berada disekitar angka satu (NTN=1), yaitu 1,5 dan mempunyai sisa pendapatan dan pengeluaran per bulan sebesar Rp. 423.375, sedangkan setelah menerima paket bantuan anggota kelompok nelayan penerima bantuan memiliki Indeks Engel 49,59% untuk makanan dan Nilai Tukar Nelayan (NTN) berada disekitar angka satu (NTN=1), yaitu 1,8, ini sudah tergolong mempunyai tingkat kesejahteraan yang cukup baik karena mereka sudah bisa memenuhi kebutuhan subsistensinya dan mempunyai potensi untuk mengkonsumsi kebutuhan sekunder atau bahkan menabung (saving) dengan sisa pendapatan dan pengeluaran per bulan sebesar Rp. 1.395.000. Kata kunci : Kelompok Nelayan, Bantuan Jaring Pajeko, Desa Dalum